2013
DOI: 10.3390/cancers5041221
|View full text |Cite
|
Sign up to set email alerts
|

Gene Regulatory Scenarios of Primary 1,25-Dihydroxyvitamin D3 Target Genes in a Human Myeloid Leukemia Cell Line

Abstract: Genome- and transcriptome-wide data has significantly increased the amount of available information about primary 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) target genes in cancer cell models, such as human THP-1 myelomonocytic leukemia cells. In this study, we investigated the genes G0S2, CDKN1A and MYC as master examples of primary vitamin D receptor (VDR) targets being involved in the control of cellular proliferation. The chromosomal domains of G0S2 and CDKN1A are 140–170 kb in size and contain one and three V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…ChIP was carried out following the protocol described earlier . After treatment of SGBS cells, nuclear proteins were cross‐linked to DNA by 10‐min formaldehyde treatment.…”
Section: Methodsmentioning
confidence: 99%
“…ChIP was carried out following the protocol described earlier . After treatment of SGBS cells, nuclear proteins were cross‐linked to DNA by 10‐min formaldehyde treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the most induced 1,25(OH) 2 D 3 target genes, such as CD14 (43.5-fold), CAMP (38.4-fold), IL8 (9.3-fold), THBD (8.8-fold), SLC37A2 (7.2-fold) and G0S2 (4.3-fold), were already characterized in the context of previous mechanistic studies as primary 1,25(OH) 2 D 3 targets [14,19,21,22,25,38,39]. The fact that the chromosomal domains of these genes contain binding sites for BCL6 suggests a positive feedback loop mechanism for the expression of the genes.…”
Section: Faire-seqmentioning
confidence: 94%
“…Interestingly, it was found that 1,25D binding shifts the locations of VDR occupation to DR3-type response elements that surround its target genes, and there was a large variety of regulatory constellations of VDR binding sites. It is also becoming increasingly clear that VDR binding choices are highly specific for the cell type [ 130 , 131 , 132 ]. The biological significance may be derived from microarray analyses following 1,25D treatment, such as that which found that the monocytic marker CD14 and cathelicidin anti-microbial peptide were by far the most markedly upregulated genes in this scenario [ 131 ].…”
Section: Signaling Pathways Studied In Hematopoietic and Myeloid Cmentioning
confidence: 99%
“…The biological significance may be derived from microarray analyses following 1,25D treatment, such as that which found that the monocytic marker CD14 and cathelicidin anti-microbial peptide were by far the most markedly upregulated genes in this scenario [ 131 ]. Among the genes upregulated early, as shown by the microarray analysis, the monocyte-specific genes and metabolism-related genes are two noticeable groups [ 132 ]. The effects of longer exposure to 1,25D include the finding that VDR binding sites are significantly enriched near autoimmune and cancer-associated genes identified from GWA studies [ 133 ].…”
Section: Signaling Pathways Studied In Hematopoietic and Myeloid Cmentioning
confidence: 99%